An Analysis of Lexical Cohesion Found in “Photograph” Song Lyrics - Ni Kadek Ayu Anggreni Putri (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
The aim of this study is to find out the type and function of lexical cohesion used in the lyrics of Ed Sheeran's song entitled